Analisis Kekuatan Sambungan Las TIG dengan Variasi Arus Listrik pada Penyanggah Tabung Pasteurisasi Berbahan Stainless Steel 201 - Alkamaluddin; Unung Lesmanah; Mochammad Basjir (Universitas Islam Malang, 2022)
Welding (Welding) is a metal joining procedure by softening some of the base metal and filler metal without regard to additional metal and produces a persistent metal. Welding has many endless types depending on the cycle and maintenance. One of the welding processes is electric curve welding which is separated into 2 classifications, namely the consumable cathode and the non-consumable terminal. Welding this time using Gas Tungsten Bend Welding or better known as Tungsten Idle Gas (TIG). TIG gas is one type of electric circle segment welding with argon gas protection. This welding is widely applied to processed steel, aluminum, responsive metals such as magnesium and titanium. This study utilizes variations in electric currents of 100 A and 130 A. From the results of the examination that has been carried out, the strength of the TIG welding joints with variations in electric current is obtained on the sanitary machine supporting cylinders made of 201 tempered steel. J/mm2, at 130 An electricity it is 5.140 J/mm2 and at 160 An electricity it is 3.676 J/mm2. In this way the best value of the effect test is at 100 A.